Human ecology education for development and sustainability the College of Human Ecology at the University of the Philippines Los Baños - Amparo, Jennifer Marie (Journal of Human Ecology, 2019)
In different parts of the world, the development and teaching of Human Ecology have taken on different and distinct disciplinal roots and development trajectories. Most published papers on the historical development of Human Ecology focus on western higher education institutions, particularly those based in the United States, Europe, and Australia. This paper aims to contribute to the dis- cussion of Human Ecology development in higher education institutions, focusing on the experience of developing countries such as the Philippines in establishing and promoting an interdisciplinary Human Ecology in the academe. In this paper, the authors set out to (1) examine the history of Human Ecology in Asia, in general, and University of the Philippines Los Baños (UPLB), in partic- ular; (2) discuss the challenges faced by the College of Human Ecology (CHE) in the development of Human Ecology in the university; and (3) identify the prospects and future directions of Human Ecology in UPLB as collaborations are continually strengthened across the International Society of Human Ecology’s network. Discussion is based on a review of related literature, personal interviews, and discussions with key Human Ecology colleagues in several workshops spanning 2007 to 2017. Key insights include the following: (1) most Human Ecology programs in Asia are local, applied, and action-oriented and were established through the evolution of Home Economics, growing global environmentalism, and institutional changes in response to these changes; (2) challenges faced by Human Ecology in UPLB include pedagogical issues for interdisciplinarity, navigating academic turfs, and securing professional recognition; and (3) current prospects of CHE include impact areas in policy and development, including its contribution to Human Ecology knowledge production and dissemination. Future directions include developing its theory- and method-building through Human Ecology graduate programs, exploring innovative transdisciplinary teaching-learning approaches, and strengthening its policy advocacy role in the region.